Integrating Energy Literacy and Computational Thinking in Secondary Education: A Rasch-Based Analysis to Support Game-Based Physics Learning - Muhamad Yusup; Sardianto Markos Siahaan; M Rokhati Harianja (Postgraduate, University of Mataram, 2025)
The urgency of global energy and environmental challenges underscores the importance of integrating energy literacy and computational thinking (CT) in secondary science education. This study investigates the impact of a digital game-based learning intervention aimed at enhancing these competencies within the physics curriculum. Using a static-group pretest-posttest design, 72 senior high school students were divided into an experimental group receiving game-based instruction and a control group experiencing conventional teaching. A 20-item multiple-choice test was developed and analyzed using the Rasch model. Findings revealed that the experimental group achieved significantly higher post-test ability scores (1.66 logits) than the control group (0.97 logits), indicating a shift toward higher ability levels. Students exposed to the game demonstrated stronger capabilities in integrating conceptual understanding of energy systems with systematic problem-solving strategies, as well as in tasks requiring advanced reasoning, pattern recognition, and abstraction. However, some high-level competencies—particularly those involving the synthesis of conceptual knowledge with algorithmic thinking—remained challenging. The results suggest that digital game-based learning can effectively foster deeper, multidimensional competencies in physics education, yet further refinements in game design, especially in scaffolding complex problem scenarios and promoting structured reflection, are essential to maximize its educational impact.